Memoria 2023 del Centro de Investigación de Agroindustria (CIA) - Instituto Nacional de Tecnología Agropecuaria (INTA). Centro de Investigación de Agroindustria (Centro de Investigación de Agroindustria, INTA, 2024)
The CIA integrates its two Institutes: The Institute of Rural Engineering and the Institute of Food Technology and is part of the National Center for Agricultural Research (CNIA) of INTA. The objectives of the CIA for the period 2021-2025 are to promote value addition in agri-food and agro-industrial production, through promoting the competitiveness of value chains within the framework of Industry 4.0. with a Bioeconomy approach, differentiating products, improving efficiency in production processes and reducing costs. Promote in the institution a culture of innovation that promotes sustainable development, in virtuous coordination with the different actors of the pentahelix (Government, University, Entrepreneurs, NGOs and Society). The programmatic themes of the CIA Institutes, within the PEI 2015-2030 of INTA, in its 2019 portfolio and the new 2023 portfolio, make this Research Center present in the demands of the Agrobioindustrial Sector (SAB). Lines of Action: Adding value to agri-food and agro-industrial production, through promoting the competitiveness of value chains. Product differentiation and increased efficiency in production processes and cost reduction. Generation of knowledge to promote wealth and employment both at the local and regional level (in coordination with other units of INTA, the National Science and Technology System and local institutions) with a solid focus on Social Responsibility. Knowledge management for innovation processes. Food safety and security. Agroelectronics and Internet of Things (IOT). Application of phytosanitary products, their use and environmental benefits. Application of advanced technologies (Nanotechnology and precision agriculture). Traditional and Renewable Energies (Biofuels, Biogas, Solar, Wind). Applied mechanics and mechanization for family farming. Agrologistics. Its activities are carried out in coordination with the other regional and research centers of INTA and inter-institutionally with public and private organizations both nationally and internationally.